Le rôle politique des revues conservatrices aux Etats-Unis depuis les années 1980 - Marie-Cécile Naves (Amnis)
The article aims at studying, through the example of Fukuyama’s theory of the « End of History », how the American journal The National Interest, as other conservative journals, has, since the mid 1980s, been a crucial media instrument for the dissemination of some ideals of the Republican Party. We have thus to think about the conditions of production and dissemination of this theory in an exceptional geopolitical and intellectual context – the end of the cold war. The changing links between American intellectuals and political power, and the issue of foreign policy since the beginning of the 1980s are the core of our research.